contestada

Ramiya is using the quadratic formula to solve a quadratic equation. Her equation is x = after substituting the values of a, b, and c into the formula. Which is Ramiya’s quadratic equation? Quadratic formula: x = 0 = x2 + 3x + 2 0 = x2 – 3x + 2 0 = 2x2 + 3x + 1 0 = 2x2 – 3x + 1

Respuesta :

Answer:


0 = x2 + 3x + 2

Ramiya's quadratic equation given her representation of the quadratic formula is x² + 3x + 2

How to solve quadratic equation using quadratic formula

Ramiya's equation:

x = StartFraction negative 3 plus or minus StartRoot 3 squared minus 4(1)(2) EndRoot Over 2(1) EndFraction

x = -3 ± √3² - 4(1)(2) / 2(1)

Quadratic formula:

x = -b ± √b² - 4ac / 2a

Therefore,

From Ramiya's equation

a = 1

b = 3

c = 2

Quadratic equation is given by

ax² + bx + c

So

x² + 3x + 2

The complete question:

Ramiya is using the quadratic formula to solve a quadratic equation. Her equation is x = StartFraction negative 3 plus or minus StartRoot 3 squared minus 4(1)(2) EndRoot Over 2(1) EndFraction after substituting the values of a, b, and c into the formula.

Which is Ramiya’s quadratic equation?

2x²+3x+1

2x²-3x+1

x²-3x+2

x²+3x+2

Learn more about quadratic equation:

https://brainly.com/question/1214333